The Web as Space to explore diversity - Raffaghelli, Juliana (Formazione & insegnamento, 2014)
Can the Net become a place suitable for promoting intercultural education? Which elements are crucial to achieving this goal? There is strong agreement on the fact that the Internet represents a metaphor for a place or environment having social significance in identity building processes (Turkle, 1996), as well as being a cultural environment promoting virtual citizenship and virtual communities (Rheingold, 1993) which, in time, can become formal learning communities capable of generating effective learning (Palloff, Pratt, 1999; Rovai, 2002b). Recently, some attention has been paid to the design of an interculturally sensitive virtual learning place, which can promote further intercultural learning (Dunn, Marinetti, 2002; Rollin, Harrap, 2005; McConnell, 2006; Edmundson, 2005; Rutheford, Kerr, 2008). The participated construction of a virtual working/learning space (VWLS) aimed at supporting an international cooperation project on Teachers’ Education, where two continents (European Union, Latin America) ten Universities from six countries (Italy, Spain, Portugal, Brazil, Paraguay, Argentina, Chile) and near 150 students from those countries and beyond is described in this article. The case study attemps to show how learning spaces on the Web can give support to dimensions that are the kernel of intercultural education, from motivation to sharing one’s own cultural and professional identity (constituted by symbols, icons, music, etc.), to collaboration across frontiers (creating professional learning communities).